Acumulação de matéria seca e produção de grãos em sorgo granífero (Sorghum bicolor (L) Moench), em função da adubação nitrogenada - Silveira Carvalho , Orozimbo; Nogueira Fontes , Luiz Antônio; Américo Cardoso, Antônio; Moura Filho , Waldemar; Defelipo, Braz Vitor (Revista Ceres, 2025)
During the 1977/78 agricultural season, field studies were carried out in Viçosa, Minas Gerais, to evaluate the influence of nitrogen fertilization on the build-up fo dry matter at successive stages of growth in the aerial parts of grain sorghum. At the same time, production and level of nutrients were evaluated.